Removal of Eosin Y Dye using Activated Carbons from Modified Wood Dust Powder of Dalbergia sisoo - Shrestha, Dibyashree (Patan Pragya, 2021)
An agro-waste/wood-dust of Dalbergia sisoo (Sisau)derived activated carbons have been applied as a potential adsorbent to remove anionic dye “Eosin Y” from aqueous solution. The activated carbons were synthesized by carbonization technique. The chemical activation was done by impregnating with three different impregnating agents, i.e. acid, base and salt, namely phosphoric acid (H3PO4) , potassium hydroxide (KOH) and sodium carbonate (Na2CO3). The prepared activated carbons were characterized by various instrumental techniques like TGA/DSC, XRD, Raman, FTIR, SEM and BET. The BET analysis gave the evidence of micropores and mesopores in the samples. The H3PO4 activated carbon sample revealed higher surface area than KOH and Na2CO3 activated samples. The amorphous nature of the sample was observed on the basis of XRD and Raman spectroscopy technique. The adsorption of dye was performed by varying the dye concentration, pH and sample dose. The maximum percent of dye removal by H3PO4 activated carbon (Dal-A) for Eosin Y was found to be 99.9 % at an aqueous solution of 20ppm, pH 3.5, adsorbent dose of 30 mg and 5 min of time as compared to KOH and Na2CO3 activated carbons; Dal-B and Dal-C respectively. This study proved to be highly successful in addressing the local problem of wastewater pollution of garment and textile industrial effluents using locally available wood dust of Dalbergia sisoo. Acidic pH environment was found to be more conducive in the removal of Eosin Y dye.